A STUDY ON PROBLEM AND CHALLENGES FACED BY PEOPLE THROUGH HEALTH INSURANCE COMPANIES IN INDIA (International Journal of Food and Nutritional Sciences, 2023)
Medical insurance is crucial, especially considering the rising expenses of healthcare services in India. As demonstrated by growing healthcare costs, diverse socioeconomic backgrounds, and evolving healthcare systems, medical insurance is an imperative necessity. This study aims to determine the Problems and challenges people face through health insurance companies. The technique used in this study is the Wilcoxon one-sample signed rank test. The findings of the study indicated Rigid procedure of claim settlement, delaying in payment to hospital, Delay in payment of claims, Complex terms in documentation, Billing errors, Coverage disputes and High Co-pay are high problems. Whereas, Delaying in operation in providing services and Lack of 24x7 support are seen to be low problems. Further studies can be conducted using exploratory factor analysis